2016
DOI: 10.3389/fmicb.2016.01913
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Characterization of Zoonotic and Veterinary Pathogens in Ticks from Northeastern China

Abstract: Tick-borne diseases are considered as emerging infectious diseases in humans and animals in China. In this study, Ixodes persulcatus (n = 1699), Haemaphysalis concinna (n = 412), Haemaphysalis longicornis (n = 390), Dermacentor nuttalli (n = 253), and Dermacentor silvarum (n = 204) ticks were collected by flagging from northeastern China, and detected for infection with Anaplasma, Ehrlichia, Babesia, and Hepatozoon spp. by using nested polymerase chain reaction assays and sequencing analysis. Anaplasma phagocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 54 publications
0
24
1
1
Order By: Relevance
“…Its main vectors are Ixodes spp. (Stuen et al 2013) but it has also been found in Haemaphysalis spp., D. nuttalli and D. silvarum in China (Wei et al 2016). In the present study, Anaplasma was not detected in I. persulcatus, most likely due to the small sample size for this tick.…”
Section: Tick-borne Pathogenscontrasting
confidence: 69%
“…Its main vectors are Ixodes spp. (Stuen et al 2013) but it has also been found in Haemaphysalis spp., D. nuttalli and D. silvarum in China (Wei et al 2016). In the present study, Anaplasma was not detected in I. persulcatus, most likely due to the small sample size for this tick.…”
Section: Tick-borne Pathogenscontrasting
confidence: 69%
“…Phylogenetic analyses were conducted using the software MEGA 5.0, and multiple sequence alignments were performed using Clustal W. The neighbour‐joining method was used to construct a phylogenetic tree, whose reliability was evaluated by the bootstrapping analysis with 1000 replicates, and the bootstrap value more than 60% was considered significant (Wei et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…It causes direct injury to suck blood, which can also cause inflammation and skin allergy, often leading to pruritus in livestock. In addition, it can transmit a variety of infectious diseases (27)(28)(29). During the peak activity seasons of 2015 to 2019, 2,256 ticks were collected using different capturing methods in each site of the project area (Figure 1).…”
Section: Discussionmentioning
confidence: 99%